Orofacial function and temporomandibular disorders in Parkinson's Disease: a case-controlled study - Sara Baram; Carsten Eckhart Thomsen; Esben Boeskov Øzhayat; Merete Karlsborg; Merete Bakke (BMC, 2023)
Abstract Background The difficulties and challenges faced by people with Parkinson's disease (PD) in performing daily orofacial function are not systematically investigated. In this study, specific orofacial non-motor and motor symptoms and functions were systematically examined in PD patients in comparison to a matched control group. Methods The clinical case-controlled study was conducted from May 2021 to October 2022 and included persons with PD and age- and gender-matched persons without PD. The participants with PD were outpatients diagnosed with PD at the Department of Neurology at Bispebjerg University Hospital in Copenhagen, Denmark. The participants underwent a systematic clinical and relevant self-assessment of the orofacial function and temporomandibular disorders (TMD). The primary outcomes were objective and subjective assessments of the general orofacial function, mastication, swallowing, xerostomia and drooling. The secondary outcomes were the prevalence of TMD and orofacial pain. The difference in outcome measures between the two groups was analysed using chi-square and Mann-Whitney U test. Results The study included 20 persons with PD and 20 age- and gender-matched persons without PD. Both objectively and subjectively, persons with PD had poorer orofacial function than the control group. Persons with PD had also a significantly more severe limitation of jaw mobility and jaw function. The objective masticatory function was also significantly reduced for persons with PD compared to the control group, and 60% of persons with PD found it difficult to eat foods with certain consistencies while 0% of the control group reported that problem. Persons with PD could swallow less water per second and the average swallowing event was significantly longer for PD persons. Even though PD persons reported more xerostomia (58% for persons with PD and 20% for control persons), they also reported significantly more drooling than the control group. Additionally, orofacial pain was more prevalent in PD persons. Conclusions Persons with PD have a compromised orofacial function. Furthermore, the study indicates a link between PD and orofacial pain. In order to screen and treat persons with PD accordingly, healthcare professionals should be aware of and address these limitations and symptoms. Trial registration The trial was approved by the Regional Committee on Research Health Ethics of the Capital Region (H-20,047,464), the Danish Data Protection Agency (514 − 0510/20-3000), and registered at ClinicalTrials.gov (NCT05356845).